INTRODUCING METHOD OF GENERALIZED DERIVATIVE CONCEPT IN MATHEMATICS - Nurgabyl, D.N.; Seitova, T.M. (Academic Scientific Journal of Computer Science, 2020)
In this paper, we consider a technique for introducing the concept of a generalized derivative function of one variable. Some assertions of combinatorics are given and proved; the concept of the derivative of the natural order is introduced using the limit of the sequence. Using the above statements, the concept of a fractional derivative is introduced. The basic properties of the fractional derivative are formulated and proved. Examples are given